Can Acceptance of Urban Shrinkage Shift Planning Strategies of Shrinking Cities From Growth to De-Growth? - Marjanović, Marjan (2024)
Shrinking cities scholars claim that planning actors in the cities where shrinking is accepted are more likely to change the focus of planning strategy from pursuing growth to actively planning for de-growth. Considering this argument, this article investigates to what extent planning actors in shrinking cities seek solutions outside the dominant growth paradigm if they accept the reality of shrinkage. This is accomplished by examining the comprehensive plans of 18 shrinking cities in the Rust Belt area of the US and establishing relations between the interpretations of urban decline expressed in these planning documents and the resulting planning visions and strategies. The findings demonstrate that although planning actors in most analysed cases accepted urban shrinkage as a reality and adopted a vision of a smaller future city, they mainly devised strategies that facilitate growth. This suggests that urban planning may be far less impacted by specific interpretations of shrinkage, including acceptance, than what is popularly believed to be the case. Instead, growth remains a focal point of most planning efforts in shrinking cities, even when planning actors acknowledge it may not be realistically attainable.